‘It’s Already Hard and It’s Nearing Impossible’: A Thematic Analysis of Submissions by Rural Veterinarians to the NSW Parliamentary Inquiry into the Veterinary Workforce Shortage - Sharon Mary Pepita Thio; Anne Quain (Veterinary Sciences)
There is a global veterinary workforce shortage, particularly in rural and regional areas. In response to this shortage in New South Wales (NSW), the State Parliament launched a Parliamentary Inquiry in 2023. The Inquiry received 205 publicly available written submissions, providing insights into the perceived challenges and barriers for veterinarians working in rural practice, and how the perceived impact of the feminisation of the workforce interacts with this. By analysing a subset of submissions written by veterinarians reporting lived experiences in rural practice (n = 63), we identified eight major themes. These were as follows: rural practices are not financially sustainable; rural veterinarians often have a more challenging and higher workload than their urban counterparts; working in rural practice increases challenges to health and wellbeing; it is difficult to recruit and retain people in rural practice; veterinary students are poorly selected and not well prepared for rural practice; clients have unrealistic expectations of rural veterinarians; rural practice is not compatible with family life; and veterinarians have mixed opinions regarding whether an increase in the proportion of female veterinarians is a key contributing factor in the shortage of veterinarians. These findings may assist in the development of recruitment and retention strategies for rural veterinary practice.